2015
DOI: 10.1039/c5ta02109j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogenation on the microwave absorption properties of BaTiO3 nanoparticles

Abstract: Microwave absorbing materials (MAMs) have numerous important applications in electronic communications, signal protection, radar dodging, etc. Although it has been proposed as a promising MAM, BaTiO 3 has a high reflection coefficient at the interface with air, causing a large reflection. Thus, its efficiency of microwave absorption is not satisfactory. Here, we report that hydrogenation has largely improved the microwave absorption of BaTiO 3 nanoparticles. Hydrogenation is performed on BaTiO 3 nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(38 citation statements)
references
References 40 publications
5
33
0
Order By: Relevance
“…A material with an RL value less than À20 dB is an excellent absorber because this value corresponds to a microwave absorption of 99.99%. 34 Therefore, we conclude that the microwave-absorbing property of carbon bres can be signicantly enhanced by BN coating through the reduction of microwave reection.…”
Section: Microwave-absorbing Propertymentioning
confidence: 76%
See 1 more Smart Citation
“…A material with an RL value less than À20 dB is an excellent absorber because this value corresponds to a microwave absorption of 99.99%. 34 Therefore, we conclude that the microwave-absorbing property of carbon bres can be signicantly enhanced by BN coating through the reduction of microwave reection.…”
Section: Microwave-absorbing Propertymentioning
confidence: 76%
“…To further describe the microwave-absorbing property of the samples, the reection loss (RL) of the carbon bres with and without BN coating was calculated in accordance with the following equations by using the single-layer model: 33,34 RLðdBÞ ¼ 20 log 10…”
Section: Microwave-absorbing Propertymentioning
confidence: 99%
“…Dong et al [159] also observed strong microwave absorption in anodized TiO 2, due to the interfacial electric field formed at the boundary of crystalline-amorphous phases. Tian et al [160] reported the good microwave absorption in hydrogenated BaTiO 3 , due to the increased resonance of polar rotations with the incident electromagnetic field. The mechanism of the strong microwave absorption in black TiO 2 nanocrystals was investigated by Li et al [161].…”
Section: Microwave Absorptionmentioning
confidence: 99%
“…As shown in Fig. 6 [48]. Therefore, these novel 3D B(OH) 3 /α-Fe 2 O 3 -CMSs are promising candidate for practical applications.…”
Section: Electromagnetic Parameter Measurementsmentioning
confidence: 96%